The (Un)importance of Somali piracy - Clark, Karen (Crime, law and social change, 2015)
Although maritime piracy off the Somali coast has garnered a lot of media attention, little scholarly work has investigated its influence in the region and its long term consequences. This paper examines the causes of piracy and how it relates to the geopolitics of the Horn of Africa. Contemporary cases of Somali piracy and their political, legal and economic impacts are reviewed both in terms of how they affect the Somali population as well as the impact on the enterprise of private global shipping. Finally, the reaction by the international community to Somalia as compared to the involvement of the stable democracy of Somaliland is discussed.